The Protestant Pervasiveness and Political Entanglement in the Vietnamese Peripheral Borderlands - Duong, Bien V.; Ngo, Dong Quoc; Nguyen, Ngoan Bich Thi; Vu, Ha Thu Ha (Indonesian Journal of Political Studies, 2025)
Protestantism is often exemplified as a religion for metropolitans; however, gaining prominence among upland dwellers in peripheral areas like remote borderlands when it was introduced to Vietnam. Generally, such peripheral areas caused less concern for the State of Vietnam in peaceful times and held little significance in the national development as well as in the national religious and cultural landscape. Nevertheless, the emergence of Protestantism there led to a series of relevant issues that seemed to forcefully compel the State’s concern. The article attempts to provide a map of the Protestant expansion in the Vietnamese peripheral borderlands over time, focusing on the period from the 1990s onward. It then emphasizes certain challenges that the pervasiveness of Protestantism in the peripheral areas may have posed to the State of Vietnam during the process of renovating society. The research further argues that the involvement of Protestant-related factors in cultural, economic, and political realms in the peripheral borderlands in Vietnam could be a point for geopolitical forces to exploit and foster the rise of peripheral nationalism there, which in turn would become greater testing to the nation-state’s efforts in keeping total control over its territory and society.